Pediatric chronic myeloid leukemia is a unique disease that requires a different approach - Hijiya, Nobuko; Schultz, Kirk R.; Metzler, Markus; Millot, Frederic; Suttorp, Meinolf (Blood, 2016)
Chronic myelogenous leukemia (CML) in children is relatively rare. Because of a lack of robust clinical study evidence, management of CML in children is not standardized and often follows guidelines developed for adults. Children and young adults tend to have a more aggressive clinical presentation than older adults, and prognostic scores for adult CML do not apply to children. CML in children has been considered to have the same biology as in adults, but recent data indicate that some genetic differences exist in pediatric and adult CML. Because children with CML may receive tyrosine kinase inhibitor (TKI) therapy for many decades, and are exposed to TKIs during a period of active growth, morbidities in children with CML may be distinct from those in adults and require careful monitoring. Aggressive strategies, such as eradication of CML stem cells with limited duration and intensive regimens of chemotherapy and TKIs, may be more advantageous in children as a way to avoid lifelong exposure to TKIs and their associated adverse effects. Blood and marrow transplantation in pediatric CML is currently indicated only for recurrent progressive disease, and the acute and long-term toxicities of this option should be carefully evaluated against the complications associated with lifelong use of TKIs.
EVALuna2:33877